Detecting dementia in patients with normal neuropsychological screening by Short Smell Test and Palmo-Mental Reflex Test: an observational study - Streit, Sven (BMC Geriatr, 2015)
BACKGROUND: General practitioners (GPs) are in best position to suspect dementia. Mini-Mental State Examination (MMSE) and Clock Drawing Test (CDT) are widely used. Additional neurological tests may increase the accuracy of diagnosis. We aimed to evaluate diagnostic ability to detect dementia with a Short Smell Test (SST) and Palmo-Mental Reflex (PMR) in patients whose MMSE and CDT are normal, but who show signs of cognitive dysfunction. METHODS: This was a 3.5-year cross-sectional observational study in the Memory Clinic of the University Department of Geriatrics in Bern, Switzerland. Participating patients with normal MMSE (>26 points) and CDT (>5 points) were referred by GPs because they suspected dementia. All were examined according to a standardized protocol. Diagnosis of dementia was based on DSM-IV TR criteria. We used SST and PMR to determine if they accurately detected dementia. RESULTS: In our cohort, 154 patients suspected of dementia had normal MMSE and CDT test results. Of these, 17 (11 %) were demented. If SST or PMR were abnormal, sensitivity was 71 % (95 % CI 44–90 %), and specificity 64 % (95 % CI 55–72 %) for detecting dementia. If both tests were abnormal, sensitivity was 24 % (95 % CI 7–50 %), but specificity increased to 93 % (95 % CI 88–97 %). CONCLUSION: Patients suspected of dementia, but with normal MMSE and CDT results, may benefit if SST and PMR are added as diagnostic tools. If both SST and PMR are abnormal, this is a red flag to investigate these patients further, even though their negative neuropsychological screening results. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12877-015-0094-0) contains supplementary material, which is available to authorized users.